IMPLEMENTASI TUNJANGAN SERTIFIKASI DAN KESEJAHTERAAN GURU DI SDN JADI SEPAKAT - Umniyatul Azizah; Panca Selly Inariska; Hasbiyallah Hasbiyallah; Aan Hasanah (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2021)
Based on the guidance of life and the needs that accompany the rapid progress of the world, the quality of human life is also progressing and increasing. In the purpose of teacher education, it is demanded to make students become knowledgeable, creative, independent human beings and so on, it also makes education providers including teachers to be better, superior and of quality. For this reason, in the welfare of teachers, the government provides a certification allowance program to reward certified teachers. The research objective was to determine certification allowances and the welfare of Indonesian teachers. The research method used qualitative analysis. The findings of this study considered the need for teacher welfare with an intensive certification allowance and providing facilities with the hope that teachers and students were equal in providing and receiving knowledge. There is a common thread in the implementation of certification allowances and teacher welfare.